Consumers' preferences for electricity-saving programs: Evidence from a choice-based conjoint study. (20th May 2019) - Hille, Stefanie; Weber, Sylvain; Brosch, Tobias
Abstract: Electric utilities play a crucial role in designing and deploying electricity conservation programs. However, because people can freely decide to participate in such programs or not, better understanding what types of programs appeal to specific groups of customers is fundamental. The authors therefore explore preferences of likely subscribers for electricity-saving programs defined by various features (such as goal setting, tailored feedback provision, or reward and penalty schemes), and use a latent class approach to capture heterogeneity and detect segments of people that share similar preferences. The segments are subsequently profiled in terms of socio-demographic and psychographic characteristics. Overall, results show that there is considerable heterogeneity in tastes for different features of electricity-saving programs. The findings allow identifying individual characteristics that influence the likelihood to adopt different forms of programs. On this basis, electric utilities may design electricity-saving programs that better satisfy customer needs and effectively tailor marketing and communication programs to the specific target groups. Highlights: A choice-based conjoint experiment is designed to elicit preferences for electricity-saving programs. Strong heterogeneity prevails in tastes for features of electricity-saving programs. No one-size-fits-all approach to design programs should therefore be followed. Psychographic variables were most powerful in explaining likely program subscription.